1997
DOI: 10.1007/s002040050402
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo- p  -dioxin (TCDD) and congeners in infants. A toxicokinetic model of human lifetime body burden by TCDD with special emphasis on its uptake by nutrition

Abstract: Contents of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and of 16 further congeners--polychlorinated dibenzodioxins and dibenzofuranes (PCDD/PCDF)--were determined in lipids of adipose tissue and of livers of 3 stillborns and of 17 infants (0.43-44 weeks old) who died from sudden infant death syndrome. International toxic equivalents (I-TEq) calculated for the sum of TCDD together with all of the 16 congeners (1.55-29.63 ng/kg lipids of adipose tissue, n = 20; 2.05-57.73 ng/kg liver lipids, n = 19) were within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(126 citation statements)
references
References 40 publications
6
116
0
4
Order By: Relevance
“…The slower elimination among women was consistent with another study that found slower elimination in women than men at the age of 60 years, a pattern the authors attributed to continued increases in BMI among older women (Kreuzer et al, 1997 ). The observed gender difference is also consistent with higher TCDD levels in women than in men 20 years after the Seveso accident ( Landi et al, 1997 ).…”
Section: Discussionsupporting
confidence: 88%
“…The slower elimination among women was consistent with another study that found slower elimination in women than men at the age of 60 years, a pattern the authors attributed to continued increases in BMI among older women (Kreuzer et al, 1997 ). The observed gender difference is also consistent with higher TCDD levels in women than in men 20 years after the Seveso accident ( Landi et al, 1997 ).…”
Section: Discussionsupporting
confidence: 88%
“…Dwernychuk et al (2002) demonstrated the apparent food-chain transfer of TCDD from contaminated soil to cultured fish pond sediments and to fish and duck tissues and finally humans, where TCDD was detected in whole blood and breast milk. Several studies reported that the half-life of dioxin in humans is 7-11 years for adults (Pirkle et al 1989;Kreuzer et al 1997). Despite the fact that a significant amount of time has passed since the end of the war, herbicide residues still exert adverse effects on those subjects living in the sprayed/hot-spot areas and on the country's ecosystem as a whole (Schecter et al 2001;Mai et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We excluded measurements collected before age 16 because childhood growth could potentially affect the compartment mobility and thus the equilibrium of serum PBB concentration levels (Wolff and Schecter, 1991). We also excluded measurements taken during pregnancy or during any period of breast-feeding because of the potential mobilization of PBB into the bloodstream during these times (Eyster et al, 1983;Kreuzer et al, 1997).…”
Section: Study Populationmentioning
confidence: 99%